A correlational study of Malaysian hoteliers' self-ratings of guest interaction skills and occupational self-efficacy before and after gamification experiences - Abdulla, Nasiha
English is widely used in the hospitality industry. With rising standards of workplace English language requirements, the demands for good oral proficiency have become a major challenge to employees. This is evident from previous researches on issues and difficulties faced by hospitality staff during guest-host exchanges. While existing researches indicate that Malaysia’s hotel industry faces similar challenges, there have been only few investigations on employees’ interaction skills and self-efficacy. Malaysian hoteliers’ perceptions of their own guest interaction skills and their relationship to occupational self-efficacy, have yet to be reported too. This study aimed to investigate Malaysian hoteliers’ perception of their own guest interaction skills and occupational self-efficacy, as well as the relationship between the two, before and after gamification experiences. A survey was administered on 173 hoteliers from a hotel in Selangor, Malaysia and from a descriptive analysis done, it was revealed that all 173 respondents had below moderate to moderate perception of their guest interaction skills and occupational self-efficacy. 12 of the total respondents were then randomly selected to attend ESP classes with gamification as part of a one-group pretest-posttest quasi–experimental research. Analyses on the sample’s ratings of their own guest interaction skills and occupational self-efficacy after gamification showed that there were positive correlations with a significant difference in how they perceive their guest interaction skills and occupational self-efficacy. The hoteliers were also found to self-rate their occupational self-efficacy higher than their guest interaction skills. The findings of this study convey to both ESP instructors and hotel managers that gamification should be used in classrooms and in-house trainings as it has positive influences on how hoteliers perceive their own abilities to perform their jobs and interact with their guests.